RNAi screen for membrane proteins that are involved in neuronal pruning in Drosophila sensory neurons - Hendrikson, Josephine (2015)
Pruning, a remodeling process that selectively remove exuberant neurons without causing cell death, is important and required for the development of precise neuronal connectivity in mature nervous system during development. In this paper, RNA interference (RNAi) screening was used to investigate the involvement of membrane proteins in dendrite pruning process in Drosophila sensory neurons. There were 7 lines of 2 genes identified to display pruning defects phenotype in their Class IV dendritic arborization neurons (ddaC) at 16 h after puparium formation (APF), namely CG10188 and CG10587. Out of the two genes, CG10587 was further characterized through immunostaining process for Ecdysone receptor isoform B1 (EcR-B1), Molecule interacting with casL (Mical) and Ubiquitin (Ub) expression. Our findings showed that this gene might regulate Mical expression and have defect in its ubiquitin-proteasome system (UPS), suggesting that it involved in ecdysone signaling pathway to cause pruning to occur. However, further investigations are required to understand its cellular and molecular mechanisms in governing dendrite pruning. In addition, further characterization should also be done for CG10188 identified. Nevertheless, our findings have served as preliminary investigation in discovering novel genes, in particular the membrane proteins, which govern dendritic pruning process.